ANALISIS TINGKAT KEPUASAN JAMAAH UMROH TERHADAP PELAYANAN PRIMA DI PT. YAMASA TOUR & TRAVEL UMROH DAN HAJI SURABAYA - jurnalpps pps; Muhammad Mashudi Azrullah; Indra Prasetyo; Mei Indrawati (Jurnal Manajerial Bisnis, 2020)
ABSTRACT The purpose of this study is to determine the level of service expected by customers from PT Yamasa Tour & Travel Umrah and Haji Surabaya and the reality of customer service from PT Yamasa Tour & Travel Umrah and Hajj Surabaya. Samples in the study amounted to 100 people of PT Yamasa Tour & Umroh and Hajj Travel Surabaya. Data Analysis in this study uses the Customer Satisfaction Index (CSI) and testing using the Importance Performance Analysist (IPA) method. The results of the study: 1) Through the calculation of the Customer Satisfaction Index (CSI), the value of CSI PT Yamasa Tour & Travel Umrah & Haji Surabaya was 80.8%which indicates that the customer satisfaction index of PT Yamasa Tour & Travel Umrah & Hajj Surabaya on Very Satisfied criteria, 2) The results of the Peformance Analysis Importance calculation indicate that the attribute the main priority agenda for performance improvement is the dimension of Empathy, that is, employees establish good relationships with the congregation and on the Responsiveness dimension, which provides quick and precise information. Keywords: customer satisfaction, excellent service, customer satisfaction index (csi), importance performance analysist (IPA).